“We Must Participate with the Fruits of Our Faith in Building Socialism”. The Preaching Committee in the Danubian Reformed Church District in the Mid-20ᵗʰ Century - SZETEY, Szabolcs (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2024)
As a result of the communist takeover in 1948, the Bishop of the Danubian Reformed Church District, László Ravasz was deposed, and Albert Bereczky took his place. In the end of 1951, Bereczky wrote a report to the general meeting of the Reformed Church in which he requested the authorization to set up a “preaching committee” with the aim of supervising sermons. He believed it was important for the pastors to talk about issues of their time in sermons because “we don’t preach in a vacuum space but to real people”. In reality, the committee’s function was the full control over pastors and the search for the ideological/theological content (which is called “narrow-road” theology) in preachings. That is why every pastor was asked to send in one sermon that was to be delivered between 1/01/1952 and 25/02/1952. József Bodonhelyi, head teacher of practical theology at the Faculty of Theology of the Reformed Church, who was also member of this preaching committee, wrote notes about these received texts and sermons where he probably appeared in person. We could find certain qualifications in his notes that seriously affected the careers of the pastors (for example, “he doesn’t address the issues of our time”; “his teaching is dangerous”; “he must urgently retire”).